1988
DOI: 10.3406/rfsp.1988.411178
|View full text |Cite
|
Sign up to set email alerts
|

Les attitudes socio-politiques des jeunes issus de l'immigration en région parisienne

Abstract: In spite of conditions of socio-economic and occupational traits similar to those of young French people belonging to the lower strata, second generation young North Africans display specific political attitudes and behavior. At the same age level and level of instruction, they show more political interest and commitment than their French-stock counterparts and are massively oriented to the left. While attachment to the Muslim religion persists, it is defined above all as a cultural and family heritage and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…SOS-Racisme recruited high school and college students of all nationalities to form local anti-racism groups. One survey in the Paris region found that 14 percent of Muslim immigrant youths were members of an anti-racism association, compared to 8 percent of Catholic immigrant youths, and 3 percent of French youths (Muxel 1988). Surveys in 1985 and 1988 found that a greater proportion of the French public had positive rather than negative perceptions of SOS-Racisme (Gastaut 2000).…”
Section: Background: Immigrant Social Movements In Francementioning
confidence: 95%
“…SOS-Racisme recruited high school and college students of all nationalities to form local anti-racism groups. One survey in the Paris region found that 14 percent of Muslim immigrant youths were members of an anti-racism association, compared to 8 percent of Catholic immigrant youths, and 3 percent of French youths (Muxel 1988). Surveys in 1985 and 1988 found that a greater proportion of the French public had positive rather than negative perceptions of SOS-Racisme (Gastaut 2000).…”
Section: Background: Immigrant Social Movements In Francementioning
confidence: 95%
“…Les travaux sur le comportement politique des musulmans sont relativement récents et assez peu développés en Belgique. En France, par contre, Muxel (1988) avait déjà abordé la question du poids de la variable de la religion auprès des jeunes issus de l'immigration. Jocelyne Cesari (2001) a également corroboré l'hypothèse du vote à gauche des musulmans français.…”
Section: Etudes Sur Le Comportement éLectoral Des Français Musulmansunclassified
“…Comme le constate Vallet en France, « les familles immigrées perçoivent le système éducatif comme une voie importante de mobilité sociale » (1996 : 25). L'incorporation des enfants d'immigrés dans la société française peut également être mesurée au travers de leur engagement politique, par exemple leur participation aux élections et leur activisme (Muxel, 1988;Richard, 1998). En raison de la discrimination continue sur le marché du travail à l'égard des immigrés et de leurs descendants, certains jeunes revigorent leurs liens avec le pays d'origine de leurs parents pour trouver des possibilités économiques et professionnelles : par exemple les enfants d'immigrés algériens entretiennent des activités commerciales avec l'Algérie qui ne requièrent pas pour eux de vivre là--bas (Santelli, 1999), alors que les enfants d'immigrés portugais poursuivent leur projet professionnel en France en conservant leur héritage culturel au travers de la maîtrise de la langue portugaise (Hily et Oriol, 1993).…”
Section: La Famille Et Les Jeunes Dans Le Contexte Migratoireunclassified